Performance of Membrane Bioreactor in Nitrogen Removal using Anammox Bacteria Cultivated from Lake Koto Baru - Zulkarnaini, Zulkarnaini; Amanda, Tiffany Azhra; Putra, Alqadri Asri; Komala, Puti Sri; Nilawati, Dewi; Widyarani, Widyarani; Sembiring, Tarzan; Mawarda, Panji Cahya; Septevani, Athanasia Amanda; Rustama, Mia Miranti; Andriyani, Rina (Makara Journal of Science, 2026)
Anaerobic ammonium oxidation (anammox) is the biological conversion of ammonium to nitrogen gas (N2) using nitrite as an electron acceptor. This study evaluated the performance of a membrane bioreactor (MBR) in nitrogen removal at room temperature using Candidatus Brocadia fulgida, an anammox bacterium previously cultivated from Lake Koto Baru, Tanah Datar, Indonesia. The MBR was operated for 48 days with a hydraulic retention time of 24 h under a continuous supply of ammonium and nitrite, with both substrates provided at influent concentrations of 70, 150, and 250 mg-N/L. Samples were collected twice a week and analyzed via UV–Vis spectrophotometry. The stoichiometric ratios of ∆NO2−-N/∆NH4+-N and ∆NO3−-N/∆NH4+-N were 1.13 and 0.15, respectively, which were consistent with the anammox reaction. The maximum nitrogen removal performance, including nitrogen removal rate, ammonium conversion efficiency, and nitrogen removal efficiency (NRE), reached 0.515 kg-N/m³∙d, 92.76%, and 91.27%, respectively, at a nitrogen loading rate of 0.566 kg-N/m³∙d. Anammox bacteria from Koto Baru Lake showed high NRE at room temperature using MBR.